2021
DOI: 10.2147/amep.s335578
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students’ Perspectives and Readiness to Transition to E-Learning During COVID-19 in the UAE: A Cross-Sectional Study

Abstract: Introduction:The 2020 COVID-19 crisis affected all sectors, including education. This study explored the experiences and challenges faced by tertiary students in the United Arab Emirates when they were suddenly required to transition from traditional classroom learning to E-learning following the outbreak of COVID-19. Methods: This cross-sectional study used mixed methods to collect and analyse qualitative and quantitative data. The participants were Nursing students involved in clinical training. Results: Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…The results are in agreement with Yekefallah et al [ 50 ], who found that female students tend to perform better, even online, than male students. Although these issues have also been confirmed by other studies [ 55 , 56 ], some authors have found no gender differences in students’ mental distress [ 57 , 58 ]. In particular, recent research by Kabir et al [ 59 ] found that e-learning readiness had a significant association with perceived e-learning stress among university students.…”
Section: Discussionsupporting
confidence: 74%
“…The results are in agreement with Yekefallah et al [ 50 ], who found that female students tend to perform better, even online, than male students. Although these issues have also been confirmed by other studies [ 55 , 56 ], some authors have found no gender differences in students’ mental distress [ 57 , 58 ]. In particular, recent research by Kabir et al [ 59 ] found that e-learning readiness had a significant association with perceived e-learning stress among university students.…”
Section: Discussionsupporting
confidence: 74%
“…Category 4: Connectivity issues E-learning platforms depend greatly on the internet; therefore both educators and students are required to have a good internet network (Minghat et al 2020:18). Previous studies conducted on the use of e-learning during the early stages of the COVID-19 pandemic revealed lack of access to good quality internet, power failure and unstable internet connection as some of the challenges experienced (Adarkwah 2020:10;Amir et al 2020:3;Divya & Binil 2021:2319Mukasa et al 2021Mukasa et al :1508. Poor internet signals in some parts of the world are because of geographical limitations, which educational institutions have no control over (Gupta et al 2020:22).…”
Section: Category 3: E-learning Is a Lonely Journeymentioning
confidence: 99%
“…A study carried out in the United Arab Emirates on nursing students' challenges relating to e-learning encountered during the COVID-19 pandemic included lack of robust internet coverage affecting students' engagement on learning activities, concerns about lack of privacy, difficulties with the teaching platforms, internet connection issues and communication difficulties. In addition, there were concerns that facilitators were slow at reacting to their needs (Mukasa et al 2021(Mukasa et al :1508.…”
Section: Introductionmentioning
confidence: 99%
“…Even with these positive findings, there were challenges reported by more than one third of participants who were unsatisfied from the e-learning; this could be explained due the lecturer was not in a real classroom, and students struggled to understand the lessons. Other students complained about a shortage of network access and computers, and some even offered that the university distributes laptops and internet access for free (Mukasa et al, 2021). And this finding is near to the study conducted by (Ali, 2017) who found that more than half of students were unsatisfied with their experience with online learning experience.…”
Section: Discussionmentioning
confidence: 78%